Electroacupuncture inhibits the corneal ROS/TXNIP/NLRP3 signaling pathway in a rat model of dry eye syndrome. Issue 1 (February 2022) - Yang, Yanting; Zhang, Dan; Wu, Lijie; Zhang, Ji; Wu, Danyan; Li, Xiying; Zhi, Fangyuan; Yang, Guang; Kong, Xiehe; Hong, Jue; Zhao, Yue; Liu, Jie; et al.
Background: Electroacupuncture (EA) treatment has been found to ameliorate clinical symptoms in patients with dry eye, but its mechanisms are still not entirely clear. Objective: To study the regulation of EA on ocular surface function and the corneal reactive oxygen species (ROS)/thioredoxin-interacting protein (TXNIP)/Nod-like receptor protein 3 (NLRP3) inflammatory signaling pathway in dry eye syndrome (DES) model rats. Methods: Male Sprague-Dawley (SD) rats were randomly divided into five groups: Normal, Model, Model + EA, Model + NAC (N-actetylcysteine) and Model + NS (normal saline). The DES model was developed by subcutaneous injection of scopolamine hydrobromide with exposure to an air draft in the latter four groups. After intervention, the Schirmer I test (SIT), tear film break-up time (BUT) and ROS content were measured, the histopathological changes of corneal tissues were observed, and the mRNA and protein expression levels of TXNIP, NLRP3, apoptosis-associated Speck-like protein containing CARD (ASC), caspase-1, interleukin (IL)-1β and IL-18 were detected. Results: Compared with the Model group, the SIT and BUT increased significantly in the Model + EA group after intervention (p < 0.05), and the corneal injury was improved. Corneal ROS content declined in both Model + EA and Model + NAC groups (p < 0.05), and mRNA expression of TXNIP, NLRP3, ASC and caspase-1 also decreased (p < 0.01). Corneal protein expression of TXNIP, NLRP3, IL-1β and IL-18 decreased significantly in the Model + EA group (p < 0.01). Conclusion: Inhibiting the ROS/TXNIP/NLRP3 signaling pathway may be the mechanism underlying the role of EA in improving corneal injury in DES model rats.